2007
DOI: 10.1002/ibd.20065
|View full text |Cite
|
Sign up to set email alerts
|

Long-standing colonic inflammation is associated with a low prevalence of diverticuli in inflammatory bowel disease patients

Abstract: Long-standing colonic inflammation in IBD patients is associated with a lower prevalence of diverticuli.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0
4

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 16 publications
2
12
0
4
Order By: Relevance
“…cells in UDD patients compared to controls, without a mucosal lymphocyte infiltration in the peridiverticular area. In contrast, Pezzilli [18] did not find abnormal levels of fecal calprotectin, a marker of colonic inflammation, in patients with UDD, while, on the other hand, recent studies have suggested that chronic mucosal inflammation could prevent recurrent acute IBD flares or its development [19].…”
Section: Discussionmentioning
confidence: 87%
“…cells in UDD patients compared to controls, without a mucosal lymphocyte infiltration in the peridiverticular area. In contrast, Pezzilli [18] did not find abnormal levels of fecal calprotectin, a marker of colonic inflammation, in patients with UDD, while, on the other hand, recent studies have suggested that chronic mucosal inflammation could prevent recurrent acute IBD flares or its development [19].…”
Section: Discussionmentioning
confidence: 87%
“…In contrast, Pezzilli et al [81] did not observe differences in fecal calprotectin concentrations between subjects with DD vs controls, though the study size was rather small (17 cases). More importantly, recent case-control studies of IBD suggest that chronic acute inflammation actually protects against DD [82,83] . The mechanisms by which this protection occurs are not yet understood, but may involve alterations to the luminal bolus, i.e.…”
Section: Inflammation and Ddmentioning
confidence: 99%
“…Eine Divertikulose ist bei chronisch-entzündlicher Darmerkrankung seltener zu beobachten [194,195]. Selbst wenn in der Biopsie Läsionen nachweisbar sind, die einer chronisch-entzündlichen Darmerkrankung ähnlich sind, ist der Nachweis solcher Läsionen nicht mit einer erhöhten Rate einer Colitis Crohn assoziiert [23,196].…”
Section: Kommentar Zu Statement 314unclassified